A novel multiplexed immunoassay for surface‐exposed proteins in plasma extracellular vesicles - Emma Tordoff; Jillian Allen; Katya Elgart; Ahmed Elsherbini; Vrinda Kalia; Haotian Wu; Erden Eren; Dimitrios Kapogiannis; Olesia Gololobova; Kenneth Witwer; Olga Volpert; Erez Eitan (Journal of Extracellular Vesicles)
Abstract Small membranous extracellular vesicles (EV) incorporate proteins and nucleic acids from the parent cell. Proteins exposed on EV surface are dictated by cellular origin and biogenesis pathway. To better understand the EV origin and function, it is important to develop methods that reveal surface protein composition of heterogeneous EV populations in culture supernatants and in biofluids. Tetraspanins CD9, CD63, and CD81 are common and abundant EV markers. However, their relative enrichment (profile) on EVs of specific cellular origins is not fully elucidated. We introduce LuminEV, a novel version of the Luminex assay for the multiplexed analysis of EV surface proteins. Optimized LuminEV reagents enable direct, specific, and sensitive measurements of EV markers in biofluids and in culture supernatants, bypassing EV isolation step. LuminEV assay for CD9, CD63, and CD81 was validated by comparing simplex and multiplex measurements, establishing linearity, spike‐in recovery, inter‐ and intra‐assay precision, and reproducibility between operators. LuminEV measurements of CD9, CD63, and CD81 in conditioned media from 15 cell lines revealed strong variations between cell types and showed high sensitivity, which enabled EV detection without prior concentration. Using tetraspanin levels as a readout, we noted suppression and induction of EV release from the cultured cells by GW6869 and monensin. Measurement of EV CD9, CD63, and CD81 in blood plasma from 70 disease‐free donors showed respective abundance of 72, 16, and 12%. CD63 displayed weak, albeit significant, negative correlation with age and was slightly lower in female samples. The assay was then used to detect cell type‐specific EV surface markers, including CD235a (erythrocytes), GAP43 (neurons), and CD68 (macrophages), and to detect differences in tetraspanin profiles between healthy and diseased donors. In summary, LuminEV offers robust and sensitive approach for multiplexed assessment of EV surface proteins, to facilitate the research into EV biology, biomarker, and therapeutic applications.